Assessing the Capacity of Flood Prone Households in West Pasaman to Reduce Flood Risk - Sari, Nia Puspita; Widyastutik, Widyastutik; Wijayanti, Pini (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
West Pasaman is a regency in Indonesia that has a high risk of flooding. Flood risk reduction through enhancing household capacity must be pursued because individuals or households are the first to be directly affected by floods. This research aims to determine the household capacity level in flood risk reduction and the associated factors. Data about household knowledge, emergency preparedness, access information, mitigation measures, livelihood diversification, and social networks is collected by a survey of the households in Nagari Aia Gadang Barat. The result shows that the capacity of households in Nagari Aia Gadang varied to low, medium, and high levels, with the most significant proportion being the medium level, namely 65%. Household capacity is positively associated with the head household's education level and total income.